Genuine open form of the pentameric ligand‐gated ion channel GLIC. (1st March 2015) - Fourati, Zaineb; Sauguet, Ludovic; Delarue, Marc
<x xml:space="preserve">Abstract</x> Pentameric ligand‐gated ion channels (pLGICs) mediate fast chemical neurotransmission of nerve signalling in the central and peripheral nervous systems. GLIC is a bacterial homologue of eukaryotic pLGIC, the X‐ray structure of which has been determined in three different conformations. GLIC is thus widely used as a model to study the activation and the allosteric transition of this family of receptors. The recently solved high‐resolution structure of GLIC (2.4 Å resolution) in the active state revealed two bound acetate molecules in the extracellular domain (ECD). Here, it is shown that these two acetates exactly overlap with known sites of pharmacological importance in pLGICs, and their potential influence on the structure of the open state is studied in detail. Firstly, experimental evidence is presented for the correct assignment of these acetate molecules by using the anomalous dispersion signal of bromoacetate. Secondly, the crystal structure of GLIC in the absence of acetate was solved and it is shown that acetate binding induces local conformational changes that occur in strategic sites of the ECD. It is expected that this acetate‐free structure will be useful in future computational studies of the gating transition in GLIC and other pLGICs.